Biology of T cells. - Galluzzi, Lorenzo; Rudqvist, Nils-Petter (International review of cell and molecular biology, 2018)
'Biology of T Cells: Part A, Volume 341' reviews and details current advances in cell and molecular biology. The IRCMB series maintains the highest standard by publishing timely topics authored by prominent cell and molecular biologists. Specialized topics in this release include TCR signaling: Molecules and mechanisms, TCR diversity: Purpose and generation, Transcriptional programs underlying T-cell differentiation and function, Surface phenotypes of CD8+ and CD4+ T cells, Co-stimulation and co-inhibition in CD8+ and CD4+ T cells, Regulated cell death and T cells, Molecular mechanisms behind T-cell priming by DCs, and more. Key Features: Publishes only invited review articles on selected topics; Authored by established and active cell and molecular biologists and drawn from international sources; Offers a wide range of perspectives on specific subjects --